THE RELATIONSHIP BETWEEN THE PROPER SIZE OF GOVERNMENT AND CENTRAL BANK INDEPENDENCE USING GROUNDED THEORY - Khosravi, Reza; Zayandehroodi, Mohsen (Revista Inclusiones, 2019)
The purpose of this study is to investigate the relationship between the proper size of government and central bank independence using the grounded theory since they are considered as important factors in the economic stability of a country. Cukierman and Army Curve indexes are used in order to test central bank independence and the proper size of government. The central bank independence and the proper size of government are completed through the banking network.